Phytoremediation and Bioconcentration of Mineral and Heavy metals in Zea mays Inter-planted with Striga hermonthica in Soils from Mechanic Village Wukari - E. A. Yerima; A. U. Itodo; R. Sha’Atob; R. A. Wuana; G. O. Egah; S. P. Ma’ajia (African Scientific Reports, 2022)
Phytoremediation involves the use of plants to remediate contaminated sites. This study evaluates the effect of phytoremediation on mineral and heavy metal concentration in agricultural soil within the vicinity of mechanic village Wukari using Zea mays interplanted with Striga hermonthica (SMV-MS), Zea mays alone (SMV-M), Zea mays inter-planted with Striga hermonthica alongside the application of fertilizer (SMV-MSF) and Zea mays alone alongside fertilizer application (SMV-MF). The bioconcentration of mineral and heavy metal and their translocation factors from the root to shoot of maize plants were estimated using empirical models. The result reveals that the efficiency of phytoextraction of the mineral and heavy metals were within the range: P (3.12 – 44.71 %), K (16.89 – 96.32 %), Mg (0.013 – 94.12 %), Mn (2.31 – 99.98 %), Si (20.92 – 52.07 %), Zn (2.74 – 21.65 %), Pb (10.44 – 100 %), Cd (0.75 – 42.85 %), Fe (7.42 – 98.57 %) and Al (19.14 – 98.69 %) respectively. The mean root and shoot bioconcentration factors (BCFs) of K, Mg, Mn and Al were greater than one indicating higher accumulation of the elements in the root and shoot of the maize plants. The root BCF of the elements was generally in the order: Mn > K > Mg > Cd > S i > Al > P > Fe > Zn > Pb while the shoot BCF was in the order: Mn > K > Mg > Al > Fe > Cd > S i > P > Zn > Pb. The mean root to shoot translocation factors (TF) of P, Mn, Zn, Pb, Cd, Fe and Al were greater than one indicating effective translocation of the elements from the root to shoots. The translocation factors were generally in the order: Fe > Al > Pb > Mn > Zn > P > Cd > Mg > S i > K.